ENSAYO Y FICCIÓN: LA DIGITALIZACIÓN DE LA MEMORIA EN LEVEL FIVE DE CHRIS MARKER - Dr. Fernando LUQUE GUTIÉRREZ (Fonseca, Journal of Communication, 2023)
Chris Marker’s cinema, recognized as one of the most representative examples of film essay, explored insistently the role of the image in the conflictive relationship between the human being and memory. From this standpoint, this paper tries to shed light on his last full-length film, Level Five (1996), where Marker updates early approaches and focuses on the consequences of the modern communication technologies and digital images on the conflict with the traumatic past.